Diesel Engine Exhaust Exposure, Smoking, and Lung Cancer Subtype Risks. A Pooled Exposure-Response Analysis of 14 Case-Control Studies - Ge, Calvin; Peters, Susan; Olsson, Ann; Portengen, Lützen; Schüz, Joachim; Almansa, Josué; Ahrens, Wolfgang; Bencko, Vladimir; Benhamou, Simone; Boffetta, Paolo; Bueno-de-Mesquita, Bas; Caporaso, Neil; et al. (American journal of respiratory and critical care medicine, 2020)
Rationale: Although the carcinogenicity of diesel engine exhaust has been demonstrated in multiple studies, little is known regarding exposure-response relationships associated with different exposure subgroups and different lung cancer subtypes.Objectives: We expanded on a previous pooled case-control analysis on diesel engine exhaust and lung cancer by including three additional studies and quantitative exposure assessment to evaluate lung cancer and subtype risks associated with occupational exposure to diesel exhaust characterized by elemental carbon (EC) concentrations.Methods: We used a quantitative EC job-exposure matrix for exposure assessment. Unconditional logistic regression models were used to calculate lung cancer odds ratios and 95% confidence intervals (CIs) associated with various metrics of EC exposure. Lung cancer excess lifetime risks (ELR) were calculated using life tables accounting for all-cause mortality. Additional stratified analyses by smoking history and lung cancer subtypes were performed in men.Measurements and Main Results: Our study included 16,901 lung cancer cases and 20,965 control subjects. In men, exposure response between EC and lung cancer was observed: odds ratios ranged from 1.09 (95% CI, 1.00-1.18) to 1.41 (95% CI, 1.30-1.52) for the lowest and highest cumulative exposure groups, respectively. EC-exposed men had elevated risks in all lung cancer subtypes investigated; associations were strongest for squamous and small cell carcinomas and weaker for adenocarcinoma. EC lung cancer exposure response was observed in men regardless of smoking history, including in never-smokers. ELR associated with 45 years of EC exposure at 50, 20, and 1 μg/m3 were 3.0%, 0.99%, and 0.04%, respectively, for both sexes combined.Conclusions: We observed a consistent exposure-response relationship between EC exposure and lung cancer in men. Reduction of workplace EC levels to background environmental levels will further reduce lung cancer ELR in exposed workers.
Keywords: dospělí; Carcinoma, Squamous Cell; odds ratio; Carcinoma, Small Cell; Female; Europe; výfukové emise vozidel; Carcinoma, Large Cell; adenokarcinom plic; Adult; ženské pohlaví; Kanada; kouření cigaret; nádory plic; lidé; Occupational Exposure; Evropa; Vehicle Emissions; velkobuněčný karcinom; inhalační expozice; Sex Factors; Canada; Male; malobuněčný karcinom; pracovní expozice; sexuální faktory; spinocelulární karcinom; Aged; Lung Neoplasms; lidé středního věku; Cigarette Smoking; senioři; mužské pohlaví; Carbon; uhlík; Adenocarcinoma of Lung; Middle Aged; Inhalation Exposure; Odds Ratio; Humans